(x)(x)+3=19

Simple and best practice solution for (x)(x)+3=19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x)(x)+3=19 equation:


Simplifying
(x)(x) + 3 = 19

Multiply x * x
x2 + 3 = 19

Reorder the terms:
3 + x2 = 19

Solving
3 + x2 = 19

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + x2 = 19 + -3

Combine like terms: 3 + -3 = 0
0 + x2 = 19 + -3
x2 = 19 + -3

Combine like terms: 19 + -3 = 16
x2 = 16

Simplifying
x2 = 16

Take the square root of each side:
x = {-4, 4}

See similar equations:

| -3x+6=-4 | | 9.6x+18-9.9x-7.8= | | 3x+5(x-2)=14 | | x+1=37+10 | | 5x^2-x+15=0 | | 3y-6=11 | | 8x+24=3x+4 | | 3x-1=29 | | 33334+3456789986= | | 12(5-x)=72 | | 3x-15=-15 | | 6t-18+8t=14t+35-8 | | 4x-6=5x+6 | | y=3-3y | | 7*-1+1= | | 7*-2+4= | | 7*-10+4= | | 5x+50=500 | | 3(x+1)=8 | | 7*0+4= | | 2(3*0+1)= | | 7x^2+66x+27=0 | | 3n-2=-26 | | 2(3x-10+1)= | | 5x^2-14=0 | | 2(3x-2+1)= | | 20x-50=25-5x | | 2(3x-1+1)= | | 9x^2-9x-4=0 | | 2x+7x-10=4x+3-2x | | u^2-3u-12=0 | | -8z-9=32 |

Equations solver categories